The Baltic : a history - North, Michael (2015)
"The Baltic is an overview of the region as a whole that deals with politics, trade, and cultures. The book is organized into ten chronological, roughly thematic chapters, with each chapter beginning with a vignette (focus) centered on a place with particular significance to the era under discussion. Throughout, the book pays close attention not only to trade and other economic issues, but also to population groups and demographic change. Significant portions of the chapters are dedicated to a treatment development of the 'Brick Gothic' architectural style, the brilliant achievements of artists such as Berndt Notke, the founding of universities, 'Nordic Romanticism', Baltic Sea tourism etc."–(Provided by publisher.)